Megalith Cultures of the Kelabit Highlands through Space and Time; Utilizing Digital Technology in Anthropological Exhibition - Yakup, Mohd Rafee; Awangko Hamdan, Awang Arshad; Hishamuddin, Siri; Sylvester Wielding, Jussem; Poline, Bala; Mohd Zamhari, Abol Hassan; Hakimi, Halim; Sarah Naemah, Aman Leong; Doris, Anak Maying (Unimas Publisher, 2018)
An exhibition entitled ‘Megalith Cultures of the Kelabit Highlands through Space and Time’ has been curated by researchers from UNIMAS and the Rurum Kelabit Sarawak in conjunction with the 12th Pesta Nukenen (Food Festival) at the Teripun Museum, Bario. The main aim is to continue to highlight one of the outstanding features of the Kelabit Highlands, which is its ‘monumental’ landscape consisting of various types of stone monuments and landscape modifications. This exhibition is held as a mean of sharing the research findings on the megaliths to the local community as well as to test the hypothesis on the carved figure by getting feedbacks from the local community and visitors. The exhibition has established a dialogue between researchers and the public, whereas it allows the researcher to reveal what is unseen beyond the hypothesis through the eyes of the public. An important feature to this exhibition is the use of both Augmented Reality and Virtual Reality whereby layers of multimedia content (e.g. videos, animated graphics and sound) are embedded to enhance the users' experiences. This will allow a visitor to watch a still image coming to life. The use of Information and Communication Technology (ICT) could be an alternative approach in anthropology and cultural study to deliver accurate perception of the representation of cultural practices and well-documented heritage.